(untitled) (Revista Brasileira de Contabilidade e Gestão, 2025)
Objective: To understand the construction and consolidation of Accounting knowledge areas in Brazil through the analysis of the production of theses defended in doctoral programs. Method: Use of qualitative methodology with the application of content analysis to the 763 theses defended from 1962 to 2022 in 16 different Graduate Programs in Accounting Sciences (GPs) in Brazil. Also taking as a basis three distinct thematic classification approaches: UnB Accounting and Governance Congress, EAA Annual Congress, and Oliveira (2002). The approaches were chosen because they present a clear description of the thematic areas and because they generate alternative results and interpretations to scenarios already investigated in previous literature. Findings: There was a predominance of the areas of Management Accounting and Financial Accounting and Finance under the three classification approaches. However, the emergence of historically less representative areas can be noted, such as Education and Research in Accounting, Public Accounting, and Third Sector Accounting. This emergence of other themes shows that the interests of doctoral students and GPs have been more diversified. Furthermore, 86% of the dissertations were defended from 2002 on. This is associated with the growth in the number of GPs in recent decades. And the USP program has 54% of doctoral dissertations defended. This is linked to its traditionalism. Contributions: Longitudinal evidence is provided on predominant themes that highlight gaps and research opportunities that can be prioritized by GPs and accounting researchers in order to develop their literature. Greater thematic pluralization of dissertations is encouraged, as well as theorizing research.